2022
DOI: 10.1155/2022/5858257
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Segment Lumbar Intervertebral Disc Nucleus Excision on the Stability of Lumbar Segmental Sagittal Plane

Abstract: At present, lumbar disc herniation has become a problem that plagues people’s health, life safety, and social and economic development. Among them, the research of lumbar disc nucleus pulposus tissue is the focus of the treatment of lumbar disc diseases. At present, the treatment methods of lumbar disc herniation are divided into conservative treatment and surgical treatment, among which surgical treatment can be divided into open surgery and minimally invasive surgery. Surgical treatment to remove the nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Single-Segment Lumbar Intervertebral Disc Nucleus Excision on the Stability of Lumbar Segmental Sagittal Plane” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Computational and Mathematical Methods in Medicine has retracted the article titled “Single-Segment Lumbar Intervertebral Disc Nucleus Excision on the Stability of Lumbar Segmental Sagittal Plane” [ 1 ] due to concerns that the peer review process has been compromised.…”
mentioning
confidence: 99%
“…Computational and Mathematical Methods in Medicine has retracted the article titled "Single-Segment Lumbar Intervertebral Disc Nucleus Excision on the Stability of Lumbar Segmental Sagittal Plane" [1] due to concerns that the peer review process has been compromised. Following an investigation conducted by the Hindawi Research Integrity team [2], significant concerns were identified with the peer reviewers assigned to this article; the investigation has concluded that the peer review process was compromised.…”
mentioning
confidence: 99%